2014
DOI: 10.1155/2014/137545
|View full text |Cite
|
Sign up to set email alerts
|

Adapting and Implementing a Community Program to Improve Retention in Care among Patients with HIV in Southern Haiti: “Group of 6”

Abstract: Objective. In Mozambique, a patient-led Community ART Group model developed by Médecins Sans Frontières improved retention in care and adherence to antiretroviral therapy (ART) among persons with HIV. We describe the adaptation and implementation of this model within the HIV clinic located in the largest public hospital in Haiti's Southern Department. Methods. Our adapted model was named Group of 6. Hospital staff enabled stable patients with HIV receiving ART to form community groups with 4–6 members to facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
2
21
1
Order By: Relevance
“…This evaluation suggests that the CARG model can be successfully implemented on a broad scale with lower levels of external support than previous pilot studies. Unlike past pilot programmes, facilities included in this evaluation had no staff dedicated to implementing CARGs and lacked the resources to routinely conduct community visits to CARG members [13,15,20,21]. Yet, our results are consistent with findings from evaluations of pilot programmes [12,20,22], and these results bode well for other countries implementing the CAG/ CARG model nationally.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This evaluation suggests that the CARG model can be successfully implemented on a broad scale with lower levels of external support than previous pilot studies. Unlike past pilot programmes, facilities included in this evaluation had no staff dedicated to implementing CARGs and lacked the resources to routinely conduct community visits to CARG members [13,15,20,21]. Yet, our results are consistent with findings from evaluations of pilot programmes [12,20,22], and these results bode well for other countries implementing the CAG/ CARG model nationally.…”
Section: Discussionsupporting
confidence: 83%
“…In the CAG model, ART clients form into groups, and group members take turns collecting ART for all members, reducing the frequency of clinic visits. Regional and national pilots in Mozambique found higher rates of retention among CAG members [10,11], and qualitative analyses and satisfaction surveys indicated positive acceptance by ART clients and healthcare workers [12][13][14][15]. These findings have led several Ministries of Health to recently incorporate the CAG model into their national guidelines [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of MSF’s strategies concluded that they “lightened the burden for both patients (reduced travel and lost income) and health system (reduced clinic attendance)” [13]. Similar studies from Haiti, Mozambique, Tanzania, Zambia, and Uganda support the efficacy of community-supported distribution [1416]. Linking HIV diagnosis (including the use of rapid diagnostics) with home- or community-based ART initiation offers further opportunity for increased coverage: a randomized trial of 16,660 Malawian adults documented a significant increase in the rate of ART initiation among those who were offered optional home initiation of HIV care after HIV self-testing (OraQuick ADVANCE® Rapid HIV-1/2 antibody test, OraSure Technologies) as compared with those offered only facility-based services after self-testing [17].…”
Section: Principles Of Community-based Therapymentioning
confidence: 98%
“…However, several previous studies conducted in Haiti showed an improvement in HIV care and ART adherence associated with group members support (Naslund et al, 2014;Kimmel et al, 2013;Severe et al, 2010). These outcomes suggest further investigations are needed to determine the components which may contribute the most to improved adherence.…”
Section: Research Questionsmentioning
confidence: 90%
“…It is possible that an improved sense of peer-support and having an environment to confidentially discuss their experience with HIV may have increased adherence in this sample (Rasschaert et al, 2014;Naslund et al, 2014;Allen et al, 2011).…”
Section: Hypothesis 3bmentioning
confidence: 95%